MANAJEMEN SPECIAL EVENT HALLYU COME ON SPECIAL MANAGEMENT OF HALLYU COME ON - Auliani Anwar; Iriana Bakti; Heru Ryanto Budiana (Metacommunication, 2018)
ABSTRACT  The tittle of this research is “Special Management of Hallyu Come On”. This study aims to determine the management event process of Hallyu Come On, namely research, planning, design, coordination, and evaluation. The method of this research is qualitative descriptive study with the paradigm of positivism. Engineering research data collection was carried out through interviews, observation, documentation and literature study. The results showed that Hansamo implement special event management process in Hallyu Come On 2016 which is a research, planning, design, coordination, and evaluation. The research phase by FGD and internet fact finding, design phase by designing event mascot, event venue decoration and publication. Planning phase with goal setting, time, place and ticketing, event concepts, event content, rundown, event tempo, performers, sponsorship, parter media, licensing and publication. Coordination phase conducted by forming committees divided into three parts namely, the core committee or the committee of the upper line, the mid-line committee and the lower line committee and then coordinate with internal parties which is internal members of Hansamo and coordinate with external parties like media partners, sponsors, Korean Association, police, PMI, residents around the location pickles, stage vendors and lighting, guest star. The conclusion of this research is Hansamo as the organizer of Hallyu Come On is good enough to carry out special event management at each phase even though there are still shortcomings, but the event runs in accordance with the planning and success of media coverage that reported Hansamo as Korean community.Keywords:  Managemenet Special Event, Hallyu Come On, Public Relations Process, Hansamo.  ABSTRAK Judul penelitian ini adalah, “Manajemen Special Event Hallyu Come On”. Penelitian ini bertujuan untuk mengetahui proses manajemen special event Hallyu Come On yang diselenggarakan oleh Hansamo Bandung – Korean Community, yakni riset, desain, perencanaan, koordinasi dan evaluasi. Metode yang digunakan dalam penelitian ini adalah studi dekriptif, dengan paradigma positifisme. Teknik pengumpulan data ini dilakukan melalui wawancara, observasi, dokumentasi dan studi kepustakaan. Hasil penelitian ini menunjukkan bahwa Hansamo menerapkan manajemen special event dalam pelaksanaan Hallyu Come On 2016 yakni, riset, desain, perencanaan, koordinasi dan evaluasi. Tahap riset yakni dengan FGD dan fact finding melalui internet, tahap desain dengan mendesain maskot, dekorasi venue acara, lighting dan publikasi, tahap perencanaan dengan penetapan tujuan, waktu, tempat dan ticketing, konsep acara, konten acara, rundown, tempo acara, pengisi acara, sponsorship, media parter, perizinan dan publikasi. Tahap koordinasi dilakukan dengan membentuk kepanitiaan yang dibagi menjadi tiga bagian yakni, panitia inti atau panitia lini atas, panitia lini tengah dan panitia lini bawah lalu berkoordinasi dengan pihak dan internal anggota Hansamo dan eksternal Media partner, sponsor, Korean Association, kepolisian, PMI, warga sekitar lokasi acar, vendor stage dan lighting, guest star. Tahap evaluasi dilakukan dua kali yaitu evaluasi acara dan evaluasi pasca acara. Simpulan dari penelitian ini adalah Hansamo sebagai penyelenggara Hallyu Come On sudah cukup baik melaksanakan manajemen special event meskipun pada setiap tahapnya terdapat kekurangan, namun acara berjalan sesuai dengan perencanaan dan berhasil mendapatkan liputan media yang memberitakan Hansamo sebagai komunitas penyuka Korea.Kata Kunci: Manajemen Special Event, Hallyu Come On, Proses Public Relations, Hansamo